The study of Information and Communication Technology Knowledge of Teacher Professional Students Phetchabun Rajabhat University - Wongsak, Pattawut; Chalermpong, Thanawat (Community and Social Development Journal, 2023)
This study intends to examine the five areas in which teacher professional students at Phetchabun Rajabhat University are knowledgeable about information and communication technologies. However, the target group used in this research was purposive sampling. In this research being an applies research, the research model to be used is quantitative research. The tools used in the study are the knowledge of information and communication technology. The statistics used in data analysis are mean (x̅), standard deviation (S.D). According to the findings, the sample group possessed solid information technology competence. In any event, the findings of a study on the technological literacy of Phetchabun Rajabhat University students majoring in teaching indicated that these students had generally strong information technology access abilities. It was discovered that pupils of instructors had the best technological understanding after classifying knowledge of access to technology into five categories, there is little utilization of creative and technological managerial abilities. From the foregoing results, it demonstrates that the information technology literacy of teaching professional students has other elements that make the skills in the very excellent and least, such as the environment of the technology users, etc.